Calculation Method for Optimizing the Bearing Capacity of Two-Layer Clay Foundation Based on Upper-Bound Limit Analysis - Lin, Xing-Chao; Zhang, Qiang; Wang, Xianzhi; Feng, Yelin; Zhu, Guina (Frontiers in Earth Science, 2022)
In this study, a foundation bearing capacity limit analysis upper-bound solution (FLU) was proposed under the theoretical framework of limit analysis. To be more specific, an optimized mathematical model based on rigid blocks discrete system was first established, with the minimum bearing capacity as the objective function, block velocity as the main variable, and the satisfaction of velocity compatibility, associated flow rule and functional equilibrium equations of adjacent blocks as main constraints. Then, using an optimization approach, the upper bound value of the foundation’s bearing capacity was obtained. On this basis, the principle of establishing the value interval of the most dangerous slip depth of the two-layer clay foundation was developed by investigating the effects of varying depths on the bearing capacity of the two-layer clay foundation. Meanwhile, an approach for calculating the bearing capacity of the two-layer clay foundation was proposed to achieve the goal of reach-ing the foundation’s minimum bearing capacity. Furthermore, using a mathematical example, the proposed ap-proach was proven to be rational.